KEMBALINYA PUSAT HIBURAN KEBUDAYAAN DI THR LOKASARI, JAKARTA BARAT - Paramitha Mauina Hartanto; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The phenomenon of degradation does not only occur in humans, but can also occur in an area. Degradation both functionally and morally occurred in the Lokasari THR area, Taman Sari District, West Jakarta. The degradation that occurs is that the area that was once known as the center of cultural entertainment in Batavia is now inversely becoming an area that is rarely touched and contains nightlife so it is considered dangerous. The aim of the project is to deal with existing degradation by turning Lokasari back into a positive cultural entertainment area and providing a place for local people to gather. It is hoped that the project will also be useful as a city magnet, a place for recreation from daily activities, and again to experience the beautiful memories they once had in the Lokasari THR area. This research uses borrowed design methods to get space programs and typology design methods to get the shape of the mass composition. From the existing background, the Lok(Art-H)sari Cultural Center is now present and is intended to revive cultural elements in the Lokasari area. The project will be a place where people can also gather, interact, and have fun. The cultural center will bring back various programs that have become Lokasari's memories by including additions and adding a touch of modern adjustments to give an interesting impression. The memory of the culture that is very attached to the area is used as a "magnet" to revive the interaction of the community and make it an inclusive entertainment center so that it can be enjoyed by all groups of people. Keywords:  Area Degradation; Cultural Center; Lokasari; Recreaction Abstrak Fenomena degradasi tidak hanya terjadi pada manusia, namun juga dapat terjadi pada sebuah kawasan. Degradasi baik secara fungsi dan moral terjadi di Kawasan THR Lokasari, Kecamatan Taman Sari, Jakarta Barat. Degradasi yang terjadi ialah kawasan yang dulunya dikenal sebagai pusat hiburan kebudayaan di Batavia, kini berbanding terbalik menjadi kawasan yang jarang terjamah dan berisi hiburan malam sehingga dianggap berbahaya. Tujuan dari proyek adalah untuk menghadapi degradasi yang ada dengan mengembalikan Lokasari menjadi kawasan hiburan kebudayaan yang positif dan menyediakan tempat bagi masyarakat sekitar untuk berkumpul. Diharapkan proyek juga bermanfaat sebagai magnet kota, tempat berekreasi dari aktivitas sehari-hari, dan kembali merasakan memori indah yang pernah mereka miliki pada kawasan THR Lokasari. Penelitian menggunakan metode desain meminjam untuk mendapatkan program ruang serta metode desain tipologi untuk mendapatkan bentuk dari gubahan massa. Berdasarkan latar belakang yang ada, Pusat Kebudayaan Lok(Art-H)sari kini hadir dan dimaksudkan untuk menghidupkan kembali unsur kebudayaan di kawasan Lokasari. Proyek akan menjadi tempat di mana masyarakat juga dapat berkumpul, berinteraksi, dan berekreasi. Pusat kebudayaan akan mengangkat kembali berbagai program yang pernah menjadi kenangan Lokasari dengan disertakan penambahan dan memasukkan sentuhan penyesuaian masa kini agar memberi kesan menarik. Kenangan akan budaya yang sangat melekat dengan kawasan digunakan sebagai “magnet” untuk menghidupkan interaksi para masyarakat dan menjadikan pusat hiburan yang inklusif sehingga dapat dinikmati oleh seluruh golongan masyarakat.